Incorporating the impact of social investments and reforms in the European Union's new fiscal framework - Zsolt M. Darvas; Lennard Welslau; Jeromin Zettelmeyer (Bruegel, 2024)
The European Union's new fiscal framework aims to incentivise public investment and reforms by offering the option to extend the four-year fiscal adjustment period to seven years, thereby lowering the average annual fiscal adjustment requirement. Investments and reforms proposed by EU countries in their national medium-term fiscal structural plans can be expected to also inform the fiscal adjustment proposed by member states. Yet, the EU lacks an agreed methodology for deciding on the potential quantitative impact of investment and reforms on the fiscal adjustment required under the new rules. We first analyse the 'investment friendliness' of the new framework. Although the incentives offered for raising investment are powerful, the bar for extending the adjustment period mainly through higher investment is high, and the design of the new rules will make it hard to actually raise investment. We next propose an approach for quantifying the impact of investment and reform on debt sustainability in the context of the new framework, taking into account uncertainty about their implementation and their economic effects. Such a methodology would also help the European Commission evaluate the impacts of recently adopted measures. Developing this methodology will require revisiting the current commonly agreed methodologies for medium- and long-term capital stock and total factor productivity projections. We illustrate the potential impact of investment on debt sustainability analyses through calculations on three social investment measures, that is, combinations of reform and public spending that aim to increase human capital and labour force participation. While the impact of individual reforms on fiscal adjustment needs is generally modest, the combined impact of several measures could be notable.
Keywords: 330